2021
DOI: 10.2147/opth.s283327
|View full text |Cite
|
Sign up to set email alerts
|

A Year of Living Dangerously: Challenges and Recommendations for Safely Performing Ophthalmic Surgery During the COVID-19 Pandemic, from Start to Finish

Abstract: The COVID-19 pandemic has forced all nations to take an active role in infection control incorporating recommendations and measures to control viral dissemination. The epidemiological impact is very diverse and dynamic, even within the same region. Scientific knowledge regarding SARS-CoV-2 continues to improve every day with protocols needing to be updated and adjusted on a regular basis. Ophthalmology is a medical specialty identified to be at high risk for several reasons: it has very close doctor-patient co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…An Argentinean ophthalmic surgical guideline (OCEBM's LoE 5) rejects huge amounts of aerosols during oculoplastic/orbital surgery, compared to those from the patient's respiratory tract, unless general anaesthesia and electrocautery are utilised. [23] However, we found that orbital retractors were a potential viral source of remote viral spread, and contamination of intraoral retractors and lamp-handle coverings (OCEBM's LoV 2b). A possible explanation is that we used bipolar electrocautery to control bleeding during oculoplastic/orbital surgery, and all MFRs were performed under general anaesthesia.…”
Section: Discussionmentioning
confidence: 87%
“…An Argentinean ophthalmic surgical guideline (OCEBM's LoE 5) rejects huge amounts of aerosols during oculoplastic/orbital surgery, compared to those from the patient's respiratory tract, unless general anaesthesia and electrocautery are utilised. [23] However, we found that orbital retractors were a potential viral source of remote viral spread, and contamination of intraoral retractors and lamp-handle coverings (OCEBM's LoV 2b). A possible explanation is that we used bipolar electrocautery to control bleeding during oculoplastic/orbital surgery, and all MFRs were performed under general anaesthesia.…”
Section: Discussionmentioning
confidence: 87%
“…Most papers were identified as expert consensus (n=56, 44.8%), followed by literature review (n=35, 28.0%). Many articles described specific recommendations for performing intubation15–19 or for certain areas, such as psychiatric services,20–22 orthopaedics,23 haemodynamic,24 intrahospital transport,25 oncology,26 27 field hospitals,28 29 paediatrics,30–34 diagnostic centres,35–37 inpatient units,38–43 endoscopy and gastroenterology centres,44–48 gynaecology and obstetrics,40 49–55 emergency units,56–60 intensive care unit40 41 56 61–68 and the most common was the surgical centres 48 61 69–99. Other articles made recommendations for the hospital service as a whole 19 58 64 100–138.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce viral spread during ophthalmological examination and surgical procedures, measures to be taken individually, apart from central and general measures, are reported. Many measures, such as triage, reducing the number of patients, social distancing, mask use, frequent cleaning of the environment, disinfection of devices, hand hygiene, disposable gloves, personal protective equipment, HEPA filters, and avoidance of aerosol-generating processes, have been reported [18][19][20] . During the pandemic period, nasolacrimal and nasal surgical procedures were not recommended due to proximity to the nasal mucosa in the ophthalmology and otolaryngology guidelines.…”
Section: Discussionmentioning
confidence: 99%